A simplified geo-cluster definition for energy system planning in Europe. (February 2019) - Kuster, Corentin; Hippolyte, Jean-Laurent; Rezgui, Yacine; Mourshed, Monjur
Abstract: The past decade has seen the development of new means of production and distribution as well as more efficient appliances and materials that limit consumption. The variety of technical solutions has increased dramatically making decision more complex when it comes to energy systems implementation. This paper presents the ongoing research on the development of geo-clusters for energy system planning in Europe. The geo-clusters have been defined following a heterogeneous set of parameters such as climate, building typologies, socio-economic indicators. Overall, 16 different parameters have been taken into account resulting in the creation of 116 geo-clusters within Europe. The outcome of this study is the design of two tools that help the user in the geo-cluster exploration. Those geo-clusters along with a technologies' library will ease solutions' selection by referring to successful implementation within the same geo-cluster.